Groza nieba. Giambattista Vico i Hermann Usener o lękowych źródłach kultury - Pawlik, Robert (Załącznik Kulturoznawczy, 2020)
For Giambattista Vico in Principi di una Scienza Nuova (1725), the process of civilization was triggered by a seemingly unimportant event – a thunder strike that filled the primitive people (bestioni) with deadly fear. From that moment, language, religion, the institution of marriage as well as social life emerged. The peculiar hypothesis that the process of civilization was initiated with a crack of thunder found its confirmation in the study by Hermann Usener, titled Keraunos (1905). Almost two centuries after Vico, the German philologist collected evidence that both the Greeks and the Romans worshiped the thunderbolt as a divinity, at first independentlyfrom Zeus and later as identified with him. Both studies contribute to the understanding of the phobic genesis of culture, and draw attention to the fact that language, art and religion can be considered as different strategies of coming to terms with the horrors of the world.